PENINGKATAN HASIL BELAJAR SISWA MELALUI PENGGUNAAN MEDIA PEMBELAJARAN GOOGLE CLASSROOM PADA MAPEL PAI DI SMPN 1 PERAK DAN AKIDAH AKHLAK DI MA ISMAILIYAH NGUSIKAN JOMBANG - Hilyah Ashoumi; Midkhal Hamid; Jauharul Eka Mawahib (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2021)
The objectives of this study were (1) to explain the appropriateness of the google classroom learning facilities as a learning media for PAI class VII at SMPN I Perak Jombang and the morals of class XI at MA Ismailiyah Ngusi Jombang. (2) explain student learning outcomes through the use of google classroom media for class VII at SMPN I Perak and class XI at MA Ismailiyah Ngusi Jombang. This type of research uses developmental research (R & D). The data sources in this study include qualitative and quantitative data sources. In the data collection technique, researchers used validation sheets, pretest and posttest questions, and questionnaire sheets. The results of the research that have been carried out state that: (1) there is a feasibility of a positive means of using google classroom, as a learning medium for students in PAI class VII at SMPN I Perak, seen from the results of the questionnaire for all aspects of 82.24% and in the moral subjects of class XI at MA Ismailiyah Ngusi Jombang the percentage of all aspects of the questionnaire was 85%. This means that the use of google classroom is appropriate as a medium for student learning at the school. (2) there is a positive influence of the use of google classroom on student learning outcomes in PAI class VII subjects at SMPN I Perak Jombang in terms of the average pretest value of 41 and posttest of 80, as well as on the subject of moral aqidah class XI at MA Ismailiyah Ngusi Jombang was seen with the average pretest score of 33 and posttest 79 and calculated using SPSS showed that the significance was <0.05. This means that the use of google classroom has a positive effect on student learning outcomes.